Literature Study: Improving Understanding of Science Concepts Using Science Comics for Elementary School Students - Nia Maulidah; Fitria Wulandari (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the increase in understanding of elementary school science concepts using media science comics. The method used in this research is qualitative research with data collection techniques, namely literature studies. The data collection technique used is by collecting and studying data on various research results from journals, theses, scientific articles, and relevant journals. The data that has been obtained, analyzed, and studied in-depth, systematically, and critically are then described in a narrative. Based on the results of research, the literature study states that the use of media science comics can improve understanding of the concept of science in elementary schools. From the results of the research analysis showed that the results of the pretest scores of students had low concept understanding in the experimental class and the control class. After being given treatment, the results of the posttest scores showed a significant increase in the experimental class